Are corporate tax incentives for investment fit for purpose? Revisiting economic principles and evidence from low- and middle-income countries - Laura Abramovsky; Nicolo Bird; Tom Harris; Yani Tyskerud; Ataklti Weldeabzgi; Yohannes Abrha Beyene; Edward Abrokwah; India Keable-Elliott (Institute for Fiscal Studies (IFS), 2018)
Corporate income tax is an important source of revenue for many low- and middle-income countries. At the same time, many such countries lose much needed revenues by providing corporate tax (and non-tax) incentives in the hope of attracting mobile business investments, incentivising specific geographic areas and industrial sectors, or addressing market failures. Many countries thus face a difficult trade-off between raising vital revenues and maintaining an attractive corporate tax environment in a world of increasingly footloose capital and international tax competition that can lead to a race to the bottom. Against this background, there is scarce evidence about the cost and benefits of tax incentives in developing countries, which hinders evidence-based policy-making. This paper, written collaboratively by IFS researchers and policy-makers from Ethiopia and Ghana, has multiple and interlinked objectives: (i) to provide an overview of tax incentives and best practices for their design grounded in economic principles, and assess how these apply to the case studies of Ethiopia and Ghana; and (ii) to understand more broadly the causal impacts of tax incentives on economic outcomes in developing countries by reviewing the relevant methodologies to conduct rigorous quantitative analysis and the existing empirical literature. Finally, we discuss the policy implications and avenues for research given the existing literature on the causal impact of tax incentives.
Keywords: 330